PENGARUH STORE ATMOSPHERE DAN RESPONSIVENESS TERHADAP KEPUASAN KONSUMEN LIVING ROOM MUTIA GARDEN - Nurazizah Nurazizah; Nur Ajijah Ritonga; Alya Sabrina Pasaribu; Abdan Masykuri; Abdillah Satia; Tulus Panjaitan; Agus Rahmadsyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
To analyze the influence of store atmosphere and responsiveness on customer satisfaction at Living Room Mutia Garden Medan, this research was conducted using a survey method among restaurant customers. Store atmosphere includes elements such as interior design, lighting, and comfortable atmosphere, while responsiveness measures the speed and accuracy of staff in serving customers. The aim is to determine whether there is a significant influence from the interaction between the atmosphere and respondents regarding user tendencies, where the combination of the two can increase user tendencies more than the sum of their parts inseparably. This research method includes primary data sources through in-depth interviews and observations of Mutia Garden Restaurant customers. Data analysis uses qualitative descriptive methods. The research results show that the store atmosphere and responsiveness at Living Room Mutia Garden are quite good, providing customer satisfaction.